Predictive value of plasma sB7-H3 and YKL-40 in pediatric refractory Mycoplasma pneumoniae pneumonia - Zhao QiuMin; Ji ShiYan; Jiang HaiPing; Lu DongMing; Qian LiFen; Zhang JingWen; Cui Yue; Lin Wei; Ge HaoYing; Gu Meng (Open Medicine)
This study investigated the clinical significance of plasma sB7-H3 and YKL-40 levels in children with refractory Mycoplasma pneumoniae pneumonia (RMPP).